Notes on the genus Draconarius Ovtchinnikov, 1999 (Araneae: Agelenidae) with description of two new species from Laos - Hoang, Quang Duy; Nophaseud, Liphone; Jäger, Peter (Zootaxa, 2025)
Two new species of the Draconarius venustus group are described from the Vang Vieng karst region of Laos: D. laosensis spec. nov. (♂♀) from various caves, and D. externus spec. nov. (♂) from the leaf litter. Detailed descriptions, illustrations and photographs of copulatory organs along with somatic features of the new species are provided. Additionally, the male palp of D. joshimath from India is illustrated in detail and the species is assigned to the D. venustus group. Distribution maps for all known records of the genus Draconarius s.l. are given along with an analysis of cave-dwelling species and its elevational distribution.